EXPLORING THE NEXUS BETWEEN CUSTOMER RELATIONSHIP MANAGEMENT (CRM), CUSTOMER BONDING, PATIEN SATISFACTTION AND PATIENT LOYALTY - Reni Septa Anggraeni; Haris Hermawan; Mohammad Thamrin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Loyalty is very important because the health center (Puskesmas) is a primary healthcare facility that provides basic services, both for patients enrolled in the BPJS Kesehatan program and for the general public. Patient loyalty depends on the implementation of customer relationship management and the creation of customer bonding, which will foster patient satisfaction. This study aims to examine the influence of customer relationship management and customer bonding on loyalty mediated by satisfaction. The research population consists of all patients visiting the health center from January to December 2024. The number of respondents is determined using Slovin's formula, totaling 100 individuals. The method used is partial least squares for analyzing the outer model and inner model tests. The results of the direct influence tests indicate that: CRM has a positive and significant effect on patient satisfaction, customer bonding has a positive and significant effect on patient satisfaction, CRM has a positive and significant effect on patient loyalty, customer bonding has a positive but not significant effect on patient loyalty, and patient satisfaction has a positive and significant effect on patient loyalty. The indirect effect test shows that patient satisfaction plays a positive and significant role in strengthening the influence of CRM on patient loyalty, and patient satisfaction also plays a positive and significant role in strengthening the influence of customer bonding on patient loyalty.